Waste reduction in multi-family construction: a comparative study - Bond, Catherine E., author; Killingsworth, John, advisor; Elliott, Jon, committee member; Conrad, Steven A., committee member; Schaller, Zachary, committee member (Colorado State University. Libraries, 2024)
In a linear economy, construction and demolition (C&D) waste is considered to have zero value and, thus, most C&D waste ends up in landfills. However, key stakeholders have begun to improve waste management practices, focusing on waste reduction, material reuse and recycling in an effort to meet Circular Economic and Zero Waste targets. Modular construction presents itself as a sustainable alternative to traditional, site-built construction, and an important component of the emergent circular economy in the built environment. The advertised advantages to modular are reduced construction time, reduced energy consumption, reduced onsite pollution, and reusability of modular units. This study compared wood framing waste during the construction of two multi-family projects – one volumetric modular and one traditional site-built. I found evidence to suggest that the volumetric modular manufacturing process allows for greater waste aversion and diversion than the site-built environment. Overall, the modular project produced 20-33 fewer tons of wood than the traditional site-built project, which, according to the methods from ​Toochi (2018)​ is approximately 10 -16.5 tons of sequestered CO2 per year. This was quantified through waste records, project plans, and site observation. This study is an important step in the growing body of work in circular economics in the built environment and the sustainability of modular construction.
Keywords: circular economy; site-built construction; waste diversion; lean construction; volumetric modular construction